2018
DOI: 10.1002/ppul.23988
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive ventilation practices in children across Europe

Abstract: The present study shows that NIV is a widespread technique in European PICUs. Practice across Europe is variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…39 While these findings have not been adjusted for other potential confounding factors such as immunosuppressed status, 40,41 we should look more closely at our practice of NIV in PARDS, particularly for those with severe hypoxemia. [41][42][43][44] Identifying when and how to use NIV in PARDS should continue to be an active area of investigation. 45 Both the Berlin and PALICC definitions created severity groups in part because therapeutic approaches should differ as a function of ARDS severity.…”
Section: Discussionmentioning
confidence: 99%
“…39 While these findings have not been adjusted for other potential confounding factors such as immunosuppressed status, 40,41 we should look more closely at our practice of NIV in PARDS, particularly for those with severe hypoxemia. [41][42][43][44] Identifying when and how to use NIV in PARDS should continue to be an active area of investigation. 45 Both the Berlin and PALICC definitions created severity groups in part because therapeutic approaches should differ as a function of ARDS severity.…”
Section: Discussionmentioning
confidence: 99%
“…9 Since there is no consensus, NIV practices are therefore widely heterogeneous. 12 This lack of consensus contrasts with the large use of NIV in infants with bronchiolitis.…”
Section: Discussionmentioning
confidence: 99%
“…First, this is a retrospective and single-center study, while NIV practices are very heterogeneous worldwide. 12 Second, some results may have not reached significance since the statistical power was limited. Third, this is an observational study conducted in a center with no local protocol regarding ventilatory management of infants with bronchiolitis, making some of our findings difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…2,24 In a recent survey conducted across several European countries, 15.5% and 20% of participating PICUs reported NIV usage in wards and ERs, respectively. 25 Moreover, recent reports from France and Finland indicate that HFNCT is increasingly utilised in paediatric wards in hospitals without ICUs with no major adverse events, with HFNCT usage outside of the ICU ranging from 53.3-86.5%. 26,27 Table 1 summarises the characteristics and outcomes of various studies evaluating the use of NIV and HFNCT in paediatric ERs and general wards.…”
Section: Application Outside Of Paediatric Intensive Carementioning
confidence: 99%
“…The European survey reported that 36.4% of participating PICUs used NIV during paediatric transport. 25 A summary of previous research evaluating the use of NIV and HFNCT during paediatric transport is presented in Table 2. [32][33][34][35][36][37][38] Unfortunately, all of the studies evaluating NIV and HFNCT outcomes during transport were observational in nature.…”
Section: Application Outside Of Paediatric Intensive Carementioning
confidence: 99%